Penerapan Media Audio Visual Keluargaku Unik Berbasis Discovery Learning Upaya Peningkatan Keterampilan Menyimak Siswa Kelas II SD N Lowungu - Rona Nida Firnanda; Panca Dewi Purwati; Altania Maulidina Salsabilla; Dwi Indah Kurnia Sari; Qorina Syafiqo Rahma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Second-grade students at SD N Lowungu demonstrated low listening skills because the learning process had not utilized engaging, age-appropriate media that could stimulate their interest and support their cognitive development. This study aimed to describe the implementation of the Keluargaku Unik audio-visual media based on the Discovery Learning model and to examine its effectiveness in improving students’ listening skills. A mixed-methods approach with a concurrent embedded design was applied, allowing quantitative and qualitative data to be collected simultaneously to produce more comprehensive findings. Learning activities were carried out through six Discovery Learning stages, enabling students to observe scenes from the video, identify important information, formulate explanations, and verify their understanding collaboratively. During implementation, students showed increased curiosity, focus, and willingness to participate in discussions. The results indicated that all students achieved scores above the minimum mastery criterion, with an average score of 92.5. Students were able to retell the story more accurately and provide logical responses to both literal and inferential questions, demonstrating improvement in cognitive processing. Qualitative observations also showed positive behavioral changes, such as improved attention span, better emotional engagement, and more active interaction with peers. Overall, the integration of contextual audio-visual media and Discovery Learning proved effective not only in enhancing listening skills but also in creating meaningful, enjoyable, and student-centered learning experiences for young learners. This study highlights the importance of innovative media in early grade language learning.